PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA - Abidatillah, Abidatillah; Faishol, Riza; Mashuri, Imam (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This research is motivated by the results of learning English subjects students are still low. Low learning outcomes are indicated by the grades of students under the Minimum Completion Criteria (KKM). The learning outcomes under the KKM certainly resulted in learning indicators also not being achieved. Learning English using audio visual media is one of the learning strategies that use a medium that can be captured by the sense of vision and can also be captured by the listener's senses. This media directs students to receive learning materials not only from one sense, because the more senses used, the more effective and efficient the learning will be so that the material can be understood by students. This study aims to determine whether or not there is an influence of audio visual media on the results of learning English. The type of research used is quantitative research with quasy experiment pattern with one group pretest-posttest design. The data collection instruments used are written tests and verbal tests to determine students' learning outcomes using audio visual media during learning. Before being used in research, this instrument was first tested for validity and reliability. Once declared valid and reliable, new instruments can be used for research. Samples in this study as many as 15 students who took it using saturated sampling techniques. This technique uses the entire population as a sample. The data analysis technique used in this study is t. Before being calculated using the t test, the data of the research results were tested prerequisites i.e. normality test and homogeneity test. Based on the calculation result, the significance data is 0.000 which is smaller than 0.05 or 0.000<0.05. T test result also shows that the t count result is -15,591and the table t is 1.77093 with the correlation index is 0.100 or t count>t table. Thus, it can be interpreted that the calculation results indicate